Film with conductive layer

The film with a conductive layer addresses point-like defects by optimizing the anti-blocking layer's particle distribution, ensuring effective anti-blocking and minimizing defects for high-definition applications.

JP2024176058APending Publication Date: 2024-12-19NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023094269
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing methods for manufacturing films with conductive layers face issues with point-like defects due to excessively large protrusions in the anti-blocking layer, which cause chipping and disconnection of the conductive pattern, especially in high-definition applications like VR displays.

Method used

A film with a conductive layer comprising a base film, an anti-blocking layer containing particles, where the area ratio of particles in the cross-section is 3% or more, and the variation coefficient of interparticle distance follows the formula Y ≦ -0.029X+0.995, ensuring effective anti-blocking properties while minimizing point defects.

Benefits of technology

The solution effectively suppresses point defects in the anti-blocking layer while maintaining anti-blocking properties, suitable for high-definition applications by adjusting the particle distribution and dispersion in the anti-blocking layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176058000001_ABST
    Figure 2024176058000001_ABST
Patent Text Reader

Abstract

To provide a film with a conductive layer suitable for suppressing occurrence of point defects in an AB layer, while securing an anti-blocking property of an anti-blocking (AB) layer.SOLUTION: A film F with a conductive layer of the present invention includes a base material film 10, an AB layer 11, and a conductive layer 12. The AB layer 11 is disposed opposite to the conductive layer 12 with respect to the substrate film 10 in a thickness direction H, and / or between the substrate film 10 and the conductive layer 12 in the thickness direction H. The AB layer 11 contains particles. An area ratio X of the particles in the cross-section of the thickness direction H of the AB layer 11 is 3% or more. The area ratio X (%) of the particles in a cross-section in the thickness direction H of the AB layer 11 and a coefficient of variation Y of the distance between the particles satisfy the following equation (1): Y≤-0.029X+0.995 (1).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film with a conductive layer. [Background technology]

[0002] Known examples of films with conductive patterns include antenna films for transmitting and receiving radio waves and films with electrode patterns for dielectrophoretic processing. Films with conductive patterns are made from films with conductive layers. Films with conductive layers include, for example, a base film and a conductive layer on the film. Films with conductive patterns can be made by patterning the conductive layer of the film with conductive layers to form a conductive pattern (antenna coil in the case of antenna films). Technology relating to films with conductive layers is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-159091 A Summary of the Invention [Problem to be solved by the invention]

[0004] A method for efficiently manufacturing a film with a conductive layer by the roll-to-roll method is, for example, as follows. First, in the roll-to-roll method, an anti-blocking (AB) layer is formed on one or both sides of a long base film. In this way, a long base film with an AB layer is obtained. The AB layer contains a binder resin and particles. The exposed surface of the AB layer has protrusions due to the presence of the particles. Next, in the roll-to-roll method, a conductive layer is formed on one side of the base film with an AB layer. In this way, a long laminated film is obtained. This laminated film has a base film (having a surface AB layer on the conductive layer side and / or a back AB layer on the opposite side of the conductive layer with respect to the base film) and a conductive layer. Next, the conductive layer in the laminated film is patterned by wet etching in the roll-to-roll method. After this, a film with a conductive pattern is cut out from the laminated film by press processing. In this manufacturing method, the AB layer suppresses blocking (sticking) between films in the roll of the laminated film.

[0005] From the viewpoint of anti-blocking properties, the more particles there are in the AB layer, the better, and the larger they are. Specifically, the more particles there are in the AB layer, the more likely it is that large protrusions will be formed on the exposed surface of the AB layer due to particle agglomerations. Also, the larger the particles in the AB layer, the more likely it is that large protrusions will be formed on the exposed surface of the AB layer. Also, the larger the protrusions, the more blocking is suppressed.

[0006] However, excessively large protrusions on the surface of the AB layer are considered to be point defects because they cause chipping and disconnection of the above-mentioned conductive pattern formed from the conductive layer. Specifically, when the surface AB layer has a protrusion that is too large, and a conductive pattern that passes over the protrusion is formed on the surface AB layer, the conductive pattern has breaks on the protrusion. When the film with conductive layer is used as an element of a pixel panel as a wiring supply material or the like, excessively large protrusions on the surface of the surface AB layer or the back AB layer are not preferred because they cause point-like display abnormalities (especially in recent years, there has been an increasing demand for high definition in VR applications, etc., and there are cases where ultra-high quality without defects of sizes that were previously acceptable is required). Regarding point defects that cause such problems, the present inventor has obtained the following findings.

[0007] The more uniform the particle distribution in the AB layer, the more the occurrence of point defects is suppressed. The degree of uneven distribution and aggregation of particles that cause point defects varies depending on the ratio of particles in the AB layer. Therefore, adjusting the ratio and dispersion state of particles in the AB layer helps suppress point defects.

[0008] The present invention provides a film with a conductive layer that is suitable for suppressing the occurrence of point defects in an anti-blocking (AB) layer while ensuring the anti-blocking properties of the AB layer. [Means for solving the problem]

[0009] The present invention [1] relates to a film with a conductive layer, the film comprising a base film, an antiblocking layer, and a conductive layer, the antiblocking layer being disposed on the opposite side of the base film to the conductive layer in the thickness direction and / or between the base film and the conductive layer in the thickness direction, the antiblocking layer containing particles, an area ratio X of the particles in a cross section of the antiblocking layer in the thickness direction being 3% or more, and the area ratio X (%) of the particles in a cross section of the antiblocking layer in the thickness direction and a coefficient of variation Y of the distance between the particles satisfy the following formula (1): Y ≦ -0.029X+0.995 (1)

[0010] The present invention [2] includes the film with a conductive layer according to the above [1], wherein the average primary particle diameter of the particles is 10 nm or more and 200 nm or less.

[0011] The present invention [3] includes the film with a conductive layer according to the above [1] or [2], wherein the content of the particles in the antiblocking layer is 3% by mass or more and 30% by mass or less. Effect of the Invention

[0012] As described above, the film with conductive layer of the present invention has an antiblocking (AB) layer containing particles on one or both sides of a base film, and the above-mentioned area ratio X of particles in the AB layer is 3% or more. Such a film with conductive layer is suitable for ensuring antiblocking properties. In addition, in the film with conductive layer, as described above, the area ratio X (%) of particles in a cross section in the thickness direction of the AB layer and the variation coefficient Y of the distance between particles (representing the variation in the distance between particles from the case where the distance between particles is all the same (value 0)) satisfy the above formula (1). Such a film with conductive layer is suitable for suppressing the above-mentioned point-like defects in the AB layer. Therefore, the film with conductive layer of the present invention is suitable for suppressing the occurrence of point-like defects in the AB layer while ensuring the antiblocking properties of the AB layer containing AB particles. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a conductive layer-attached film of the present invention. [Diagram 2] 2 illustrates a method for producing the conductive layer-attached film shown in Fig. 1. Fig. 2A illustrates an antiblocking layer forming step, and Fig. 2B illustrates a conductive layer forming step. [Diagram 3] This shows the case where the conductive layer in the conductive layer-attached film is patterned. [Figure 4]FIG. 2 is a schematic cross-sectional view of a modified example of the conductive layer-attached film shown in FIG 1. In this modified example, the antiblocking layer is disposed between the base film and the conductive layer in the thickness direction. [Diagram 5] This is a schematic cross-sectional view of another modified example of the conductive layer-attached film shown in Fig. 1. In this modified example, the antiblocking layer is disposed on the opposite side of the base film to the conductive layer in the thickness direction, and between the base film and the conductive layer in the thickness direction. [Figure 6] 1 is a graph plotting the measurement results of the particle area ratio X (%) and the variation coefficient Y of interparticle distance in the antiblocking layer for each of the conductive-layer-attached films of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] As shown in FIG. 1, the conductive layer-attached film F of one embodiment of the conductive layer-attached film of the present invention includes a base film 10, an AB layer 11 (antiblocking layer), and a conductive layer 12. Specifically, the conductive layer-attached film F includes the AB layer 11, the base film 10, and the conductive layer 12 in this order in the thickness direction H. The conductive layer-attached film F extends in a direction (plane direction) perpendicular to the thickness direction H. The conductive layer-attached film F is, for example, a laminated film for producing a conductive pattern-attached film. Examples of the conductive pattern-attached film include a base film with an electrode pattern for dielectrophoresis processing, and an antenna film for transmitting and receiving radio waves (having an antenna coil as a conductive pattern).

[0015] The base film 10 is a base material that ensures the strength of the conductive layer-attached film F. The base film 10 has a first surface 10a and a second surface 10b opposite to the first surface 10a. The base film 10 is, for example, a transparent resin film having flexibility. Examples of the material of the base film 10 include polyester resin, polyolefin resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer. Examples of the acrylic resin include polymethacrylate. From the viewpoints of transparency and strength, the material of the base film 10 is preferably polyester resin, and more preferably PET.

[0016] The thickness of the base film 10 is preferably 30 μm or more, more preferably 70 μm or more, and even more preferably 100 μm or more, from the viewpoint of ensuring the strength of the conductive layer-attached film F. The thickness of the base film 10 is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 150 μm or less, from the viewpoint of ensuring the handleability of the base film 10 in the roll-to-roll system.

[0017] The total light transmittance (JIS K 7375-2008) of the base film 10 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, from the viewpoint of ensuring good light transmittance in the base film 10 and the conductive layer-attached film F. The total light transmittance of the base film 10 is, for example, 100% or less.

[0018] The first surface 10a and / or the second surface 10b of the substrate film 10 may be subjected to a surface modification treatment. Examples of the surface modification treatment include a corona treatment, a plasma treatment, an ozone treatment, a primer treatment, a glow treatment, and a coupling agent treatment.

[0019] The AB layer 11 is disposed on the first surface 10a side of the base film 10. That is, the AB layer 11 is disposed on the opposite side of the base film 10 to the conductive layer 12 in the thickness direction H. In this embodiment, the AB layer 11 is disposed on the first surface 10a. That is, the AB layer 11 is in contact with the first surface 10a in this embodiment.

[0020] The AB layer 11 is an anti-blocking layer for suppressing blocking (sticking) between films in a roll of the conductive layer-equipped film F. The AB layer 11 has a surface 11a on the side opposite to the base film 10. The surface 11a is exposed in the conductive layer-equipped film F.

[0021] The AB layer 11 is a cured product of a curable resin composition. The curable resin composition contains a curable resin and particles (antiblocking particles). That is, the AB layer 11 contains a curable resin and particles.

[0022] Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin. These curable resins may be used alone or in combination of two or more. From the viewpoint of ensuring high hardness of the AB layer 11, it is preferable to use at least one selected from the group consisting of acrylic urethane resin and acrylic resin as the curable resin.

[0023] Examples of the curable resin include ultraviolet-curable resins and thermosetting resins. The ultraviolet-curable resin is preferred as the curable resin because it can be cured without high temperature heating and therefore helps improve the production efficiency of the conductive layer-attached film F.

[0024] Examples of the particles include inorganic oxide particles and organic particles. Examples of the inorganic oxide particle material include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of the organic particle material include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate. The particles are preferably inorganic oxide particles, and more preferably silica particles and / or zirconia particles.

[0025] The average primary particle diameter (D50) of the particles is preferably 10 nm or more, more preferably 25 nm or more, and even more preferably 30 nm or more, from the viewpoint of the antiblocking property of the AB layer 11. The antiblocking property of the AB layer 11 depends on the height of the protrusions on the surface 11a. The larger the particles of the AB layer 11, the greater the height of the protrusions on the surface 11a tends to be. The average primary particle diameter of the particles is preferably 200 nm or less, more preferably 150 nm or less, even more preferably 100 nm or less, even more preferably 70 nm or less, and even more preferably 50 nm or less, from the viewpoint of suppressing point defects (too large protrusions) on the surface 11a. The average primary particle diameter (D50) of the particles is the median diameter in the volume-based particle size distribution (the particle diameter at which the volume cumulative frequency reaches 50% from the small diameter side), and is determined, for example, based on the particle size distribution obtained by a laser diffraction / scattering method.

[0026] The ratio of particles in the AB layer 11 (solid content of the curable resin composition) is preferably 3 mass % or more, more preferably 5 mass % or more, and even more preferably 10 mass % or more, from the viewpoint of antiblocking properties of the AB layer 11. The ratio of particles in the AB layer 11 is preferably 30 mass % or less, more preferably 20 mass % or less, and even more preferably 17 mass % or less, from the viewpoint of suppressing particle aggregation and suppressing point defects on the surface 11a.

[0027] From the viewpoint of ensuring the antiblocking property of the layer, the thickness of the AB layer 11 is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and particularly preferably 0.8 μm or more. From the viewpoint of ensuring the transparency of the AB layer 11, the thickness of the AB layer 11 is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.

[0028] The height of the protrusions on the surface 11a of the AB layer 11 is preferably 50 nm or more, more preferably 60 nm or more, and even more preferably 70 nm or more, from the viewpoint of suppressing blocking in the roll of the film with conductive layer F. The height of the protrusions on the surface 11a is preferably 120 nm or less, more preferably 100 nm or less, and even more preferably 90 nm or less, from the viewpoint of suppressing point defects on the surface 11a. In the film with conductive layer F, whether the protrusions on the surface 11a become point defects depends on the application of the film with conductive layer F, specifically, on the thickness of the conductive layer 12. The protrusion height is the distance in the thickness direction H from the flat surface on the surface 11a of the AB layer 11 to the top of the protrusion protruding from the flat surface. Such a protrusion height can be measured, for example, as follows.

[0029] First, a sample for cross-sectional observation capable of observing the cross-sectional shape of the surface 11a of the AB layer 11 is prepared by FIB (Focused Ion Beam) processing. Next, the sample is subjected to cross-sectional SEM observation and imaged by a focused ion beam scanning electron microscope (product name: "Helios G4 UX", manufactured by FEI). In the observation, the acceleration voltage is set to 1 kV, the observation image is a secondary electron image, and the direct magnification is set to 70,000 times so that the observation field is about 2 μm square. Then, the height of a protrusion (a protrusion having a shape protruding from the surrounding flat surface) is measured by image analysis software (product name: "Image J", manufactured by Wayne Rasband) when the observation image includes the protrusion.

[0030] The particle area ratio X in the cross section of the AB layer 11 in the thickness direction H is 3% or more, more preferably 5% or more, even more preferably 7% or more, and even more preferably 9% or more, from the viewpoint of the antiblocking property of the conductive layer-attached film F. The particle area ratio X is preferably 40% or less, more preferably 30% or less, and even more preferably 26% or less, from the viewpoint of suppressing particle aggregation and suppressing point defects on the surface 11. The method of measuring the particle area ratio X in the AB layer 11 is as described later in the Examples. The particle area ratio X can be adjusted, for example, by adjusting the particle content in the cured resin layer 11.

[0031] The particle area ratio X (%) and the variation coefficient Y of the interparticle distance in the cross section of the AB layer 11 in the thickness direction H satisfy the following formula (1). The variation coefficient Y of the interparticle distance represents the variation of the interparticle distance from the case where all interparticle distances are the same (value 0). A method for measuring the variation coefficient Y of the interparticle distance in the AB layer 11 is as described later in the Examples. Examples of methods for adjusting the variation coefficient Y of the interparticle distance include selecting the type of solvent contained in the resin composition for forming the cured resin layer 11 and adjusting the amount of the solvent. Examples of methods for adjusting the variation coefficient Y of the interparticle distance include adjusting the process conditions during coating of the resin composition for forming the cured resin layer 11 and the drying conditions (such as the drying temperature) after coating.

[0032] Y ≦ -0.029X+0.995 (1)

[0033] The conductive layer 12 is disposed on the second surface 10b side of the base film 10. In this embodiment, the conductive layer 12 is disposed on the second surface 10b. That is, in this embodiment, the conductive layer 12 is in contact with the second surface 10b.

[0034] The conductive layer 12 is a layer formed from a conductive material. Examples of the conductive material include metals and metal oxides. Examples of the metal include copper, silver, nickel, chromium, iron, titanium, and alloys thereof. Examples of the metal oxide include indium-containing composite oxides. The conductive material is preferably a metal, more preferably copper.

[0035] The thickness of the conductive layer 12 is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, and particularly preferably 50 nm or more, from the viewpoint of reducing the resistance of the conductive layer 12 and from the viewpoint of preventing chipping or breakage due to protrusions on the surface 11a of the conductive layer 12. The thickness of the conductive layer 12 is preferably 1000 nm or less, more preferably 500 nm or less, even more preferably 300 nm or less, and particularly preferably 200 nm or less, from the viewpoint of preventing warping of the conductive-layer-attached film F.

[0036] From the viewpoint of ensuring low resistance, the resistivity of the conductive layer 12 is preferably 1×10 -3 Ω cm or less, preferably 0.5×10 -3 Ω cm or less, more preferably 0.1×10 -3 The resistivity of the conductive layer 12 is, for example, 1×10 -8 Ω·cm or more.

[0037] The total light transmittance (JIS K 7375-2008) of the conductive layer-attached film F is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more, from the viewpoint of ensuring good light transmittance in the conductive layer-attached film F. The total light transmittance of the conductive layer-attached film F is, for example, 100% or less.

[0038] The conductive layer-attached film F is produced by a roll-to-roll method, for example, as follows.

[0039] First, as shown in FIG. 2A, the AB layer 11 is formed on the first surface 10a of the base film 10 (AB layer formation step). In this step, a curable resin composition for forming the AB layer is first prepared. The curable resin composition contains the above-mentioned curable resin and particles (antiblocking particles), and a solvent. Examples of the solvent include methyl isobutyl ketone (MIBK), ethyl acetate, and toluene. As the solvent, preferably, at least one selected from MIBK and / or ethyl acetate is used, and more preferably, MIBK is used. The solid content concentration of the curable resin composition is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, from the viewpoint of ensuring the dispersibility of the particles in the cured resin layer 10 and reducing the above-mentioned coefficient of variation Y, and is also preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less. From the viewpoint of the antiblocking property of the AB layer 11, the ratio of particles in the solid content of the curable resin composition is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. The proportion of particles in the solid content of the curable resin composition is preferably 30 mass % or less, more preferably 20 mass % or less, and even more preferably 17 mass % or less, from the viewpoint of ensuring the dispersibility of the particles in the cured resin layer 10 and reducing the above-mentioned coefficient of variation Y.

[0040] In this step, a coating film is then formed by applying a curable resin composition onto the first surface 10a of the substrate film 10. From the viewpoint of ensuring the dispersibility of particles in the cured resin layer 10 and reducing the above-mentioned coefficient of variation Y, the thickness of the coating film is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and particularly preferably 0.8 μm or more, and is also preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.

[0041] Next, the coating film on the substrate film 10 is dried. From the viewpoint of ensuring the dispersibility of the particles in the cured resin layer 10 and reducing the above-mentioned coefficient of variation Y, the drying temperature is preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 75° C. or higher, and is also preferably less than 120° C., more preferably 110° C. or lower, and even more preferably 105° C. or lower. The drying time is, for example, 20 seconds or longer, and, for example, 2 minutes or shorter.

[0042] When the curable resin composition contains an ultraviolet-curable resin, the coating film is then cured by ultraviolet irradiation, whereas when the curable resin composition contains a thermosetting resin, the coating film is cured by heating.

[0043] 2B, a conductive layer 12 is formed on the base film 10 (conductive layer forming step). Specifically, a film of a conductive material is formed on the second surface 10b of the base film 10 by a sputtering method to form the conductive layer 12. The conductive layer 12 thus formed is a sputtered film.

[0044] In this manner, the conductive layer-attached film F can be produced.

[0045] In the film F with a conductive layer, as shown in Fig. 3, the conductive layer 12 can be patterned to form a conductive pattern 12'. The conductive layer 12 can be patterned by etching the conductive layer 12 through a predetermined etching mask. Examples of the conductive pattern 12' include an electrode pattern for dielectrophoresis processing and an antenna coil of an antenna film.

[0046] As described above, the film with conductive layer F has the AB layer 11 containing antiblocking particles (the above-mentioned area ratio X of the AB particles in the AB layer 11 is 3% or more). Such a film with conductive layer F is suitable for ensuring antiblocking properties.

[0047] In addition, in the film F with conductive layer, as described above, the particle area ratio X (%) and the variation coefficient Y of the distance between particles in the cross section of the AB layer 11 in the thickness direction H satisfy the above formula (1). Such a film F with conductive layer is suitable for suppressing the above-mentioned point defects. Specifically, as shown in the examples and comparative examples described later.

[0048] Therefore, the conductive layer-attached film F is suitable for suppressing the occurrence of point defects in the AB layer 11 while ensuring the antiblocking properties of the AB layer 11 containing the antiblocking particles.

[0049] The AB layer 11 may be disposed between the base film 10 and the conductive layer 12 in the thickness direction H, as shown in FIG. 4. In this modification, the AB layer 11 is disposed on the second surface 10b of the base film 10. That is, the AB layer 11 is in contact with the second surface 10b. The conductive layer 12 is disposed on the surface 11a of the AB layer 11. That is, the conductive layer 12 is in contact with the surface 11a. Such an AB layer 11 can also function as an antiblocking layer in the conductive-layer-attached film F.

[0050] As shown in FIG. 5, the conductive layer-attached film F may include AB layers 11A and 11B as the AB layer 11. The AB layer 11A is an AB layer 11 arranged on the opposite side of the conductive layer 12 with respect to the base film 10 in the thickness direction H, and is similar to the AB layer 11 shown in FIG. 1. The AB layer 11B is an AB layer 11 arranged between the base film 10 and the conductive layer 12 in the thickness direction H, and is similar to the AB layer 11 shown in FIG. 4. The conductive layer 12 is arranged on the surface 11a of the AB layer 11B. That is, the conductive layer 12 is in contact with the surface 11a of the AB layer 11B. Both of the AB layers 11A and 11B can function as antiblocking layers in the conductive layer-attached film F. EXAMPLES

[0051] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0052] Example 1 First, 85 parts by mass of an ultraviolet-curable acrylic urethane resin composition (product name: "AICA ITRON Z844-22-HL", manufactured by AICA Kogyo Co., Ltd.), 15 parts by mass of silica particles (product name: "CSZ9281", manufactured by CIK Nanotech Co., Ltd.) having an average primary particle diameter (D50) of 30 nm, and methyl isobutyl ketone (MIBK) as a solvent were mixed to prepare a first curable resin composition having a solid content concentration of 30% by mass. The ratio of particles in the solid content of the first curable resin composition was 15% by mass. In addition, a second curable resin composition for forming a high refractive index layer was prepared. The second curable resin composition contains an acrylic ultraviolet-curable resin composition containing 51% by mass of zirconia particles having an average primary particle diameter of 40 nm, and a predetermined solvent.

[0053] Next, a first curable resin composition was applied to one side of a polyethylene terephthalate (PET) film (product name: "Lumirror U483", thickness 125 μm, manufactured by Toray) as a base film to form a coating film having a thickness of 1.8 μm. Next, the coating film was dried. The drying temperature was 100° C., and the drying time was 30 seconds. Next, the coating film was cured by irradiating with ultraviolet light in an atmospheric air. In this manner, a first cured resin layer having a thickness of 1.8 μm was formed as an anti-blocking layer (AB layer formation process). In addition, a second curable resin composition was applied to the other side of the PET film to form a coating film, and then the coating film was dried to form a second cured resin layer (high refractive index layer with a refractive index of 1.64) having a thickness of 1.0 μm (high refractive index layer formation process). In this manner, a base film with a cured resin layer was produced.

[0054] Next, a 100 nm thick Cu layer was formed as a conductive layer on the second cured resin layer of the substrate film with the cured resin layer by sputtering (conductive layer formation step). In the sputtering, a roll-to-roll sputtering deposition device (a winding-type DC magnetron sputtering device) was used. The sputtering deposition device is equipped with a deposition chamber in which a deposition process can be carried out while the substrate film with the cured resin layer is run by the roll-to-roll method. The conditions for sputtering deposition are as follows:

[0055] After evacuating the deposition chamber of the sputtering deposition apparatus, Ar was introduced into the deposition chamber as a sputtering gas, and the pressure in the deposition chamber was increased to 3.0×10 -3 Torr. The running speed of the substrate film with the cured resin layer in the device was 2.0 m / min. A copper target was used as the target. A DC power supply was used as the power supply for applying voltage to the target. The output of the DC power supply was 3.7 kW. The film formation temperature (the temperature of the substrate film with the cured resin layer on which the Cu layer is laminated) was 40°C.

[0056] In this manner, a long conductive layer-attached film (in the form of a roll) was produced for Example 1. The conductive layer-attached film for Example 1 has a laminated structure in which a first cured resin layer (thickness 1.8 μm, containing silica particles) as an antiblocking layer, a base film (thickness 125 μm), a second cured resin layer (thickness 1.0 μm, containing zirconia particles) as a high refractive index layer, and a Cu layer (thickness 100 nm) are laminated in this order.

[0057] Comparative Example 1 A film with a conductive layer of Comparative Example 1 was produced in the same manner as the film with a conductive layer of Example 1, except for the following. In the preparation of the first curable resin composition, the solid content concentration of the first curable resin composition was set to 23 mass% by adjusting the amount of MIBK added. In the AB layer formation step, the thickness of the coating film of the first curable resin composition formed on the PET film was set to 1.2 μm, the drying temperature of the coating film was set to 80° C., and the thickness of the first cured resin layer formed was set to 1.2 μm.

[0058] Example 2 First, an ultraviolet-curable acrylic urethane resin composition (product name: Lioduras TYAB-M110-01, containing 5% by mass of silica nanoparticles, manufactured by Toyochem Co., Ltd.) was mixed with MIBK to prepare a third curable resin composition with a solid content concentration of 35% by mass. The proportion of particles in the solid content of the third curable resin composition was 5% by mass.

[0059] Next, the third curable resin composition was applied to one side of a PET film (Lumirror U483, thickness 125 μm) as a base film to form a coating film having a thickness of 2.3 μm. Next, the coating film was dried. The drying temperature was 80° C., and the drying time was 30 seconds. Next, the coating film was cured by irradiating with ultraviolet light in an air atmosphere. In this manner, a first cured resin layer having a thickness of 2.3 μm was formed as an anti-blocking layer (AB layer forming step). On the other side of the PET film, a second cured resin layer (high refractive index layer with a refractive index of 1.64) having a thickness of 1.0 μm was formed in the same manner as described above with respect to Example 1 (high refractive index layer forming step). In this manner, a base film with a cured resin layer was produced.

[0060] Thereafter, a Cu layer having a thickness of 100 nm was formed as a conductive layer on the first cured resin layer in the cured resin layer-attached substrate film in the same manner as in the conductive layer-forming step described above in relation to Example 1. In this manner, a film with a conductive layer of Example 2 was produced.

[0061] Example 3 The conductive layer-attached film of Example 3 was produced in the same manner as the conductive layer-attached film of Example 2, except for the following: In the preparation of the third curable resin composition, the solid content concentration of the third curable resin composition was set to 23 mass% by adjusting the amount of MIBK added. In the AB layer formation step, the thickness of the coating film of the third curable resin composition formed on the PET film was set to 1.1 μm, and the thickness of the first cured resin layer formed was set to 1.1 μm.

[0062] Example 4 The conductive layer-attached film of Example 4 was produced in the same manner as the conductive layer-attached film of Example 2, except for the following. In the preparation of the third curable resin composition, the solid content concentration of the third curable resin composition was set to 23 mass% by adjusting the amount of MIBK added. In the AB layer formation step, the thickness of the coating film of the third curable resin composition formed on the PET film was set to 1.1 μm, the drying temperature was set to 120° C., and the thickness of the first cured resin layer formed was set to 1.1 μm.

[0063] Comparative Example 2 First, a fourth curable resin composition with a solid content concentration of 23% by mass was prepared by mixing an ultraviolet-curable acrylic urethane resin composition (product name: Lioduras TYAB-M110-02, containing 2% by mass of silica nanoparticles, manufactured by Toyochem Co., Ltd.) with MIBK. The proportion of particles in the solid content of the fourth curable resin composition was 2% by mass.

[0064] Next, the fourth curable resin composition was applied to one side of a PET film (Lumirror U483, thickness 125 μm) as a base film to form a coating film having a thickness of 1.1 μm. Next, the coating film was dried. The drying temperature was 80° C., and the drying time was 30 seconds. Next, the coating film was cured by irradiating with ultraviolet light in an air atmosphere. In this manner, a first cured resin layer having a thickness of 1.1 μm was formed. On the other side of the PET film, a second cured resin layer (high refractive index layer with a refractive index of 1.64) having a thickness of 1.0 μm was formed in the same manner as described above with respect to Example 1 (high refractive index layer forming step). In this manner, a base film with a cured resin layer was produced.

[0065] Thereafter, a Cu layer having a thickness of 100 nm was formed as a conductive layer on the first cured resin layer in the cured resin layer-attached substrate film in the same manner as in the conductive layer-forming step described above in relation to Example 1. In this manner, a film with a conductive layer of Comparative Example 2 was produced.

[0066] <Particle area ratio X> The area ratio X of particles in a cross section in the thickness direction of the cured resin layer was measured for each of the conductive-layer-attached films of Examples 1 to 4 and Comparative Examples 1 and 2. Specifically, it is as follows.

[0067] First, a sample for cross-sectional observation capable of observing the cross-sectional shape of the cured resin layer surface was prepared by FIB processing. Next, the sample was subjected to cross-sectional SEM observation and imaged using a focused ion beam scanning electron microscope (product name "Helios 600", manufactured by Thermo Fisher Scientific). In the observation, the acceleration voltage was 1 kV, the observation image was a secondary electron image, and the direct magnification was set to 5000 times so that the objective observation field was 20 μm × 25 μm square. Then, the area ratio of particles in the entire thickness direction of the cured resin layer was measured for each pixel in the width direction of the observation field using image analysis software (product name "Image J", manufactured by Wayne Rasband), and the average value of the measured values ​​in the width direction of the observation field was calculated as the particle area ratio. The values ​​are shown in Table 1.

[0068] <Coefficient of variation Y of interparticle distance> The coefficient of variation Y of interparticle distance in the cross section in the thickness direction of the first cured resin layer was measured for each of the conductive-layer-attached films of Examples 1 to 4 and Comparative Example 1. Specifically, it is as follows.

[0069] First, a sample for cross-sectional observation capable of observing the cross-sectional shape of the surface of the first cured resin layer was prepared by FIB processing. Next, the sample was subjected to cross-sectional SEM observation and imaged using a focused ion beam scanning electron microscope (product name "Helios 600", manufactured by Thermo Fisher Scientific). In the observation, the acceleration voltage was 1 kV, the observed image was a secondary electron image, and the direct magnification was set to 5000 times so that the objective observation field of view was 20 μm × 25 μm square. Then, the variation coefficient Y of the interparticle distance was obtained by image analysis of the observed image. For the image analysis, the image analysis software "Image J" (manufactured by Wayne Rasband) was used. Specifically, it is as follows.

[0070] First, the particles (black) and the resin region (white) in the cured resin layer are binarized and separated (step 1). Next, a circle (inscribed circle) is drawn (step 2) that is centered on a point (pixel) arbitrarily selected between the particles (resin region) and is tangent to the particle. Next, the second step is performed for all points (pixels) in the resin region, and if the circles overlap, the larger circle is left and the smaller circle is not left (step 3). Next, a histogram is generated for the diameters of all the remaining circles, with the class being the diameter (μm), the class width being 0.05 (μm), and the frequency being the frequency (%) (step 4). The frequency is the frequency of the number of circles. Next, based on this histogram, the average value x and standard deviation σ of the interparticle distance are calculated (step 5). Next, the standard deviation σ of the interparticle distance is divided by the average value x of the interparticle distance to obtain the coefficient of variation Y (=σ / x) of the interparticle distance (step 6). The values ​​are shown in Table 1.

[0071] FIG. 6 is a graph plotting the measurement results of the particle area ratio X (%) and the variation coefficient Y of the interparticle distance in the first cured resin layer of each of the conductive layer-attached films of Examples 1 to 4 and Comparative Example 1. In the graph of FIG. 6, the horizontal axis represents the particle area ratio X (%), and the vertical axis represents the variation coefficient Y of the interparticle distance. In FIG. 6, plots E1 to E4 represent the measurement results of Examples 1 to 4, and plot C1 represents the measurement result of Comparative Example 1. The straight line L1 is a straight line of Y=-0.029X+0.995. The plots E1 to E4 (Examples 1 to 4) are located below the straight line L1, and the plot C1 (Comparative Example 1) is located above the straight line L1. That is, each of the conductive layer-attached films of Examples 1 to 4 satisfied the following formula (1), and the conductive layer-attached film of Comparative Example 1 did not satisfy the following formula (1). The conductive layer-attached films of Examples 1 to 4 showed good results in the evaluation of point defects described below. In contrast, the conductive layer-attached film of Comparative Example 1 did not show good results in the evaluation of point defects.

[0072] Y ≦ -0.029X+0.995 (1)

[0073] <Point defects> The number of point-like defects was checked for each of the conductive layer-attached films of Examples 1 to 4 and Comparative Examples 1 and 2. Specifically, a specified defect inspection device was used to check the number of point-like defects in the conductive layer-attached films with the following device settings and settings for detected defects. Then, protrusions with a height of 3 μm or more in an observation area (2 cm square) were counted as point-like defects. As a result, the number of point-like defects in each of the conductive layer-attached films of Examples 1 to 4 was 0, and the number of point-like defects in the conductive layer-attached film of Comparative Example 1 was 20.

[0074] [Device Settings] Shooting range: 2cm x 2cm Magnification of objective lens: 20x Magnification of eyepiece lens: 10x (total magnification with objective lens: 200x) Transmission / Reflection: Reflection measurement Pixel size of captured image (effective size): 0.7μm / pixel Scan speed: 2.5mm / min

[0075] [Settings for detecting defects] Minimum size of maximum ferret diameter: 1μm Maximum size of maximum ferret diameter: 100μm Minimum size of the smallest ferret diameter: 1μm Maximum size of minimum ferret diameter: 100μm Minimum ratio of maximum to minimum Ferret diameter (maximum Ferret diameter / minimum Ferret diameter): 1 Maximum ratio of maximum to minimum ferret diameter (maximum ferret diameter / minimum ferret diameter): 1.3

[0076] <Anti-blocking properties> The anti-blocking property was evaluated for each of the conductive layer-attached films of Examples 1 to 4 and Comparative Examples 1 and 2. Specifically, the presence or absence of Newton's rings (patterns of optical interference at the interface between the COP film and the conductive layer-attached film in this test) was observed when a cycloolefin polymer (COP) film (thickness 100 μm, manufactured by Zeon Corporation) was pressed against the first cured resin layer side surface (surface opposite to the conductive layer) of the conductive layer-attached film. The anti-blocking (AB) property of the conductive layer-attached film was evaluated as "good" when no Newton's rings were observed, and as "poor" when Newton's rings were observed. The results are shown in Table 1. The conductive layer-attached film of Comparative Example 2 had a particle area ratio X of 2.23% in the first cured resin layer, and the AB property was poor.

[0077] [evaluation] The particle area ratio X, the coefficient of variation Y of the interparticle distance, and the number of measured point defects for the conductive layer-attached films of Examples 1 to 4 and Comparative Examples 1 and 2 reveal the following. The degree of uneven distribution and aggregation of particles that cause point defects varies depending on the ratio of particles in the anti-blocking (AB) layer. Therefore, point defects can be suppressed by adjusting the ratio and dispersion state of particles in the AB layer. In addition, if the number of particles in the particle-containing first cured resin layer is too small, anti-blocking properties cannot be obtained in the layer.

[0078] [Table 1] [Explanation of symbols]

[0079] F Conductive layer film H Thickness direction 10. Base film 10a 1st page 10b 2nd side 11 AB layer (anti-blocking layer) 11a surface 12 Conductive layer

Claims

1. A film with a conductive layer comprising a base film, an antiblocking layer, and a conductive layer, the antiblocking layer is disposed on the opposite side of the base film to the conductive layer in the thickness direction and / or between the base film and the conductive layer in the thickness direction; the antiblocking layer contains particles, an area ratio X of the particles in a cross section of the antiblocking layer in the thickness direction is 3% or more; A film with a conductive layer, wherein an area ratio X (%) of the particles in a cross section of the antiblocking layer in the thickness direction and a variation coefficient Y of the distance between the particles satisfy the following formula (1): Y ≦ -0.029X+0.995 (1)

2. The film with a conductive layer according to claim 1 , wherein the particles have an average primary particle size of 10 nm or more and 200 nm or less.

3. 3. The film with a conductive layer according to claim 1, wherein a content ratio of the particles in the antiblocking layer is 3% by mass or more and 30% by mass or less.

Citation Information

Patent Citations

  • Film provided with transparent conductive layer

    JP2015159091A